KEEFEKTIFAN MODEL TEAM GAMES TOURNAMENT BERBANTU POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR MATERI MEMBIASAKAN PERILAKU PANCASILA KELAS V SD - Pramesty, Recha Ardhita; Rahmawati, Intan; Sary, Ryky Mandar (Jurnal Sarjana Ilmu Pendidikan, 2025)
This research is based on the low learning outcomes of Pancasila Education subjects that have not reached the KKTP of grade V students, namely 75. This is due to the lack of use of varied learning models and learning media. Therefore, innovation in learning Pancasila Education is needed, one of which is the Team Games Tournament model assisted by interactive powerpoint. This study aims to identify whether or not the Team Games Tournament model aided by interactive powerpoint is effective on learning outcomes on the material of getting used to Pancasila behavior in grade V elementary schools. This research was conducted at an elementary school located in Sedayu Village, Gemuh District, Kendal Regency in the 2024/2025 academic year. The population in this study were all fifth grade students totaling 29. This study uses a quantitative approach with the type of pre-Experimental Design research with the form of One-Group Pretest-Posttest Design. Based on the results of data analysis, the percentage of students' completeness has increased from 0% of students who did not reach KKTP before being treated to 86.21% of the number of students who completely reached KKTP after being treated using the Team Games Tournament model assisted by interactive powerpoint media. So the Team Games Tournament model assisted by interactive powerpoint is effective on the learning outcomes of Pancasila Education material on getting used to the behavior of Pancasila class V marked by the acquisition of student learning outcomes 86,21% of the number of students against Criteria for Achievement of Learning Objectives.Keywords: Learning outcomes; Team Games Tournament; Interactive Powerpoint